Implementasi Nilai-Nilai Kebangsaan Berbasis Pancasila Dalam Mengacu Peran Manajemen Sekuriti Terhadap Perilaku Konsumen Pada Pengguna Marketplace Tiktok Shop - Syira, Syahdina Damayari; Soesanto, Edy; Sari, Dewi Puspita (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Security Management is a systematic process for managing and protecting organizational assets from various threats, both internal and external. TikTok Shop is a marketplace that is integrated with the TikTok social media platform, which has experienced rapid growth in the number of users and transactions. However, data security and consumer privacy are still key issues that have a significant influence on consumer behavior. This research aims to analyze how big a role security management plays in consumer behavior among users of the TikTok Shop marketplace based on the values contained in Pancasila. This research uses a qualitative method which is carried out by conducting a literature review of scientific articles, journals and books. The research results show that Pancasila has an important role, which refers to security management having an important role in shaping consumer perceptions and trust in TikTok Shop. The dimensions of data security and privacy, as well as ease of access to security information, are the main factors influencing consumer behavior. There are Pancasila values that play a role in Security Management and influence consumer behavior, such as; Security and Protection, Justice and Welfare, Order and Discipline, as well as Cooperation and Unity. By integrating Pancasila values in creating a better environment for TikTok Shop users. Increasing the transparency of security information and easy access to privacy information can increase consumers' positive perceptions of the platform.